Determining factors related to impaired spinal and hip mobility in patients with axial spondyloarthritis: longitudinal results from the DESIR cohort - PD, Carvalho (2021)
Objective To investigate the determinants of impaired spinal and hip mobility in patients with early axial spondyloarthritis (axSpA). Methods Five-year longitudinal data from the DEvenir des Spondyloarthrites Indifferenciees Recentes (DESIR) cohort were analysed. Associations were investigated using generalised estimating equations, using Bath Ankylosing Spondylitis Metrology Index (BASMI) linear or each of the five components of BASMI as dependent variables, and clinical and demographic variables as independent variables in univariable models. Multivariable analyses were performed, adjusting for potential confounders. Results Data from 644 patients and 5152 visits were analysed. Higher BASMI values were independently and positively associated with Ankylosing Spondylitis Disease Activity Score C reactive protein (ASDAS-CRP) (adjusted B (adjB)=0.21; 95% CI=0.15 to 0.28), MRI spinal inflammation score (adjB=0.11; 95% CI=0.04 to 0.19), enthesitis score (adjB=0.02; 95% CI=0.01 to 0.04) and age (adjB=0.02; 95% CI=0.01 to 0.03). All BASMI components were independently associated with ASDAS-CRP and MRI spinal inflammation, except for maximal intermalleolar distance (reflecting hip mobility), which was not associated with MRI spinal inflammation. Conclusion In early axSpA, spinal mobility impairment is independently determined by clinical disease activity, MRI spinal inflammation, enthesitis and age. The influence of spinal inflammation prevails in early axSpA, as opposed to spinal structural damage, which may become more relevant in later disease stages.